2013
DOI: 10.1128/jcm.02882-12
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Combining Blood Culture and SeptiFast Data for Predicting Complicated Bloodstream Infections Caused by Gram-Positive Bacteria or Candida Species

Abstract: Management of complicated bloodstream infections requires more aggressive treatment than uncomplicated bloodstream infections.We assessed the value of follow-up blood culture in bloodstream infections caused by Staphylococcus aureus, Enterococcus spp., Streptococcus spp., and Candida spp. and studied the value of persistence of DNA in blood (using SeptiFast) for predicting complicated bloodstream infections. Patients with bloodstream infections caused by these microorganisms were enrolled prospectively. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…To investigate whether dormant bacteria are present, we thus need culture‐independent methods, of which ultramicroscopic (e.g. Domingue et al ., ; Domingue, , ; Domingue & Woody, ; Ewald, ; Green, Heidger Jr & Domingue, , b ; Mattman, ; Potgieter et al ., ) and molecular sequence‐based methods (Amar et al ., ; Cherkaoui et al ., ; Fernández‐Cruz et al ., ; Gaibani et al ., ; Grif et al ., , b ; C.L. Liu et al ., ; Moriyama et al ., ; NIH HMP Working Group et al ., ; Nikkari et al ., ; Sakka et al ., ; Sato et al ., ; Valencia‐Shelton & Loeffelholz, ; Woyke, Doud & Schulz, ) are by far the most common.…”
Section: Step –1: a Dormant Blood And Tissue Microbiomementioning
confidence: 98%
“…To investigate whether dormant bacteria are present, we thus need culture‐independent methods, of which ultramicroscopic (e.g. Domingue et al ., ; Domingue, , ; Domingue & Woody, ; Ewald, ; Green, Heidger Jr & Domingue, , b ; Mattman, ; Potgieter et al ., ) and molecular sequence‐based methods (Amar et al ., ; Cherkaoui et al ., ; Fernández‐Cruz et al ., ; Gaibani et al ., ; Grif et al ., , b ; C.L. Liu et al ., ; Moriyama et al ., ; NIH HMP Working Group et al ., ; Nikkari et al ., ; Sakka et al ., ; Sato et al ., ; Valencia‐Shelton & Loeffelholz, ; Woyke, Doud & Schulz, ) are by far the most common.…”
Section: Step –1: a Dormant Blood And Tissue Microbiomementioning
confidence: 98%
“…18 The sensitivity and specificity of the LightCycler Õ SeptiFast PCR test in this current study were similar to those reported in recent studies conducted in Germany and Spain. 19,20 The Spanish group evaluated patients with complicated bloodstream infections and reported a sensitivity of 56.0% and a specificity of 79.5%. 20 It should be noted that in all these studies including the current study, 14,[18][19][20] BC results were used as the reference gold standard, even though the sensitivity of this standard diagnostic methods is also limited.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, different reference standards have been used in studies assessing sepsis tests. Some have used blood culture results alone as gold standard [20,28], whereas others have considered all pathogenic findings detected by any method [16,29]. We assessed the performances of blood culture and the two NAATs by classifying all findings judged as clinically relevant as "true positives".…”
Section: Discussionmentioning
confidence: 99%